2012
DOI: 10.1258/ijsa.2012.012047
|View full text |Cite
|
Sign up to set email alerts
|

Differences in implementation of HIV/AIDS clinical research in developed versus developing world: an evidence-based review on protease inhibitor use among women and minorities

Abstract: The aim of this revision is to evaluate ethnicity and gender rate of enrolment in registrative clinical trials of the protease inhibitors (Pls) from 1996 to 2009. Company-sponsored, phase II or III registrative clinical trials of PIs were evaluated. Forty-nine clinical trials were included. Clinical trials were conducted in centres in North America (n = 39), Central-South America (n = 22), Europe (n = 22), Africa (n = 8), Asia (n = 5), Australia (n = 10). Overall mean age was 39.6 years; median proportion of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…The number of randomised trials in Sub-Saharan Africa remains low, even though the majority of people living with HIV are treated in this low-resource setting. 23 The OCTANE trials 12,24 were some of the first and largest randomised controlled trials to compare PIs with NNRTIs in Africa, but only included females. The OCTANE Trial 1 indicated that NVP was inferior to LPV/r as an initial ART among women with prior single-dose NVP exposure, 24 in accordance with later findings from the Democratic Republic of Congo.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…The number of randomised trials in Sub-Saharan Africa remains low, even though the majority of people living with HIV are treated in this low-resource setting. 23 The OCTANE trials 12,24 were some of the first and largest randomised controlled trials to compare PIs with NNRTIs in Africa, but only included females. The OCTANE Trial 1 indicated that NVP was inferior to LPV/r as an initial ART among women with prior single-dose NVP exposure, 24 in accordance with later findings from the Democratic Republic of Congo.…”
Section: A C C E P T E Dmentioning
confidence: 99%